Light metals 2021 : 50th anniversary edition - Perander, Linus (Minerals, metals & materials series, 2021)
The Light Metals symposia at the TMS Annual Meeting & Exhibition present the most recent developments, discoveries, and practices in primary aluminum science and technology. The annual Light Metals volume has become the definitive reference in the field of aluminum production and related light metal technologies. The 2021 collection includes contributions from the following symposia: Alumina and Bauxite Aluminum Alloys, Processing, and Characterization Aluminum Reduction Technology Aluminum Reduction Technology Across the Decades: An LMD Symposium Honoring Alton T. Tabereaux, Halvor Kvande and Harald A. ye Cast Shop Technology Electrode Technology for Aluminum Production.